Enhanced mechanical and thermoelectric properties enabled by hierarchical structure in medium-temperature Sb2Te3 based alloys. (December 2020) - Qin, Haixu; Zhu, Jianbo; Li, Ning; Wu, Haijun; Guo, Fengkai; Sun, Sibo; Qin, Dandan; Pennycook, Stephen J.; Zhang, Qian; Cai, Wei; Sui, Jiehe
Abstract: (Bi, Sb)2 Te3 based materials have been commercially utilized in the field of solid refrigeration, but their application on power generation requires further improvement of thermoelectric and mechanical properties at elevated temperatures. This work reveals a kind of high-performance and robust Sb2 Te3 based alloys operating above 550 K. Starting with the optimized composition In0.1 Sb1.9 Te3, nanograins and nanotwins are constructed by high energy ball milling and some boron particles are added to impede the boundary softening caused by the grain refinement. On this basis, oversaturated copper (Cu) doping is employed to introduce both point defects and nanoprecipitates, further leading to a full-spectrum phonon scattering and extraordinary low lattice thermal conductivity. Besides, some Cu atoms replace Sb atoms to increase the carrier concentration and thus suppress the intrinsic excitation, while some others locate at twin boundaries as interstitials to accelerate the carrier migration between two adjacent twin variants, collectively contributing to significant improvement of power factor. Ultimately, the zT value of Cu0.015 B0.05 In0.1 Sb1.885 Te3 is increased above 1.0 between 573 and 673 K. This material is very suitable for segmentation with optimized Bi0.5 Sb1.5 Te3 alloys well operating at lower temperatures, leading to high device ZT exceeding 1.05 within 330–673 K, as well as high conversion efficiency up to 12.7% under temperature difference of 370 K. Graphical abstract: Image 1 Highlights: Hierarchical structure is introduced to suppress lattice thermal conductivity. Cu doping simultaneously optimizes carrier concentration and mobility. High zT above 1.0 is achieved in a wide temperature range of 573–673 K. Segmented design is proposed to produce high conversion efficiency of 12.7%.